Dari Petani Subsisten Ke Ekonomi Pasar : Studi Kasus Petani Kelapa Sawit di Kecamatan Parindu Sanggau Kalimantan Barat - Arkanudin, Arkanudin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Independent oil palm plantations in the region are extensive compared to other local crop production. Oil palm has become an important plantation product for local communities. Oil palm plantations significantly change the socio-economic and environmental conditions of local communities. Oil palm plantations in the sub-district contribute significantly more to plantation production than other small-scale crops. The purpose of this study was to investigate and analyze the transition of small-scale agriculture to a market economy and to determine the factors driving this change. This research was conducted in Parindu sub-district, considering that oil palm plantations account for 61.33% of the area. This research uses a qualitative descriptive method. Sampling was done using target sampling. Data collection techniques were conducted through observation, in-depth interviews, and documentation. The triangulation technique was used to check the validity of the data. The data analysis method used the Miles and Hubermen analysis model (data reduction, presentation, and review). The informants in this study were independent oil palm farmers. The research found that before the introduction of market-oriented commercial farming systems, the Parindu community practiced subsistence farming, shifting cultivation and rubber plantations, and the results were sufficient to meet the needs of their families. They did not cultivate rubber as their main job, but as a side job in between their work as farmers. The desire to fulfill family needs became a strong foundation for the transformation of the agricultural economy from subsistence farming to the field of product marketing through the market economy. This change affected farmers' lifestyles, which were reflected in their possessions and assets. Property and wealth clearly increase honor and dignity as well as social status.